PAKEM: Salah Satu Upaya Negara dalam Melindungi Agama‎ - Fachrizal Afandi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
The regulation to prevent blasphemy of religion is due to long experience of many cases of blasphemy which created civil unrest and in turn threatened the very fabric of society and nation. The state under the office of attorney general then created an institution named the Surveillance of People Beliefs. Its main task is to take any measures necessary to prevent the breaching of blasphemy of religion.